Tetrahexcarbon: A two-dimensional allotrope of carbon - Ram, Babu; Mizuseki, Hiroshi (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
A two-dimensional structurally stable carbon allotrope is predicted using first-principles calculations. This unique network is composed of tetra and hexa-rings of carbon atoms known as Tetrahexcarbon. Tetrahexcarbon has a quasiparticle (QP) direct band gap of 3.70 eV at G, which is closer to the ZnS, a well-known direct bandgap semiconductor. Interestingly, it is dynamically stable and can withstand temperature up to 1000 K, which is confirmed by performing phonon and ab initio molecular dynamics (AIMD) simulations. The mobilities of both electrons and holes in this material are found to be anisotropic. It exhibits extraordinary room temperature in-plane electron mobility of order similar to 10(4) cm(2)V(-1)s(-1), which is an order of magnitude higher than the black phosphorus monolayer (similar to 10(3) cm(2)V(-1)s(-1)) and two orders of magnitude higher than MoS2 (similar to 200 cm(2)V(-1)s(-1)) monolayer. The optical response of Tetrahexcarbon obtained by applying Bethe-Salpeter equation (BSE) to include excitonic effects on top of the partially self-consistent GW(0) calculation. The absorption onsets strongly depend on the light polarization directions indicating Tetrahexcarbon an anisotropic material. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: TOTAL-ENERGY CALCULATIONS; HIGH-MOBILITY; GRAPHENE; PLANAR; SEMICONDUCTORS; EXCITATIONS; PREDICTIONS; TRANSISTORS; TRANSITION; GRAPHYNE